From authentic form to symbolic meaning: a visual psychophysical framework for evaluating contemporary buildings in urban context - Kizilkan, Gozde; Arabacioglu, Feride Pinar (TAYLOR & FRANCIS LTD, 2026)
Contemporary architecture in rapidly globalizing cities faces the challenge of balancing visual recognition with contextual and cultural identity. While the visual and symbolic roles of buildings have drawn attention, a methodological gap persists in linking measurable physical attributes with perceived symbolic meaning. This study addresses that gap by proposing two-phased psychophysical framework employing a mixed-method approach that integrates quantitative visual appearance analysis across urban and building scales with qualitative visual perception based on human responses. In the first phase, the physical attributes of contemporary buildings, focusing on dimension, massing, complexity, are identified through archival review, silhouette drawings, and field observations. In the second phase, perceptual responses are captured by Semantic Differential Scale from 202 participants, including both architects and non-architects. Findings reveal that symbolic meaning arises not merely from size and scale or iconic narratives but from contextual coherence, originality, continuity, and perceived connection to local pattern. By synthesizing objective and subjective dimensions, this research establishes an empirically grounded and transferable framework for interpreting the relationship between authentic form and symbolic meaning in contemporary architecture. The framework contributes to the understanding of how buildings can enhance visual recognition, offering valuable insights for culturally responsive design strategies in globalizing urban contexts.
Keywords: Contemporary architecture; visual appearance; visual perception; symbolic meaning; psychophysical framework; ARCHITECTURE; PRINCIPLE; IMPACT; Construction & Building Technology